RHBDF2-Regulated Growth Factor Signaling in a Rare Human Disease, Tylosis With Esophageal Cancer: What Can We Learn From Murine Models? - Hosur, Vishnu; Farley, Michelle L.; Low, Benjamin E.; Burzenski, Lisa M.; Shultz, Leonard D.; Wiles, Michael V. (Frontiers in Genetics, 2018)
Tylosis with esophageal cancer syndrome (TOC) is a rare autosomal dominant proliferative skin disease caused by missense mutations in the rhomboid 5 homolog 2 (RHBDF2) gene. TOC is characterized by thickening of the skin in the palms and feet and is strongly linked with the development of esophageal squamous cell carcinoma. Murine models of human diseases have been valuable tools for investigating the underlying genetic and molecular mechanisms of a broad range of diseases. Although current mouse models do not fully recapitulate all aspects of human TOC, and the molecular mechanisms underlying TOC are still emerging, the available mouse models exhibit several key aspects of the disease, including a proliferative skin phenotype, a rapid wound healing phenotype, susceptibility to epithelial cancer, and aberrant epidermal growth factor receptor (EGFR) signaling. Furthermore, we and other investigators have used these models to generate new insights into the causes and progression of TOC, including findings suggesting a tissue-specific role of the RHBDF2-EGFR pathway, rather than a role of the immune system, in mediating TOC; and indicating that amphiregulin, an EGFR ligand, is a functional driver of the disease. This review highlights the mouse models of TOC available to researchers for use in investigating the disease mechanisms and possible therapies, and the significance of genetic modifiers of the disease identified in these models in delineating the underlying molecular mechanisms.